Analisa Kinerja Pada Sistem Alat Peraga AC Inverter Tipe Wall Split Kapasitas 0,5 PK - Aris Jujur Prasetyo; Hafid Wihangga; Miftachul Ulum; Diana Rahmawati; Riza Alfita; Rosida Vivin Nahari (FORTEI Regional VII Jawa Timur, 2022)
— Indoor air conditioning and conditioning systems are used to maintain indoor air temperature. Equipment in the air conditioning system (Air Conditioner), functions to regulate room temperature and regulate air humidity. The purpose of this research and development is to understand how it works along with its characteristics and to find out the performance produced from the AC (Air Conditioner) teaching aid system that has been made. Besides that, the making of this teaching aid is also used as a learning medium on AC system electricity material in a real form which is applied as a practicum medium so that it has a high level of effectiveness. The research method used was to carry out the preparatory stage by searching for literature and field studies, then designing the model and assembling the test equipment. An air conditioning machine with a vapor compression cycle has several main components, namely a compressor, condenser, capillary tube, evaporator and filter. The AC trainer model with an inverter type with a capacity of 0.5 PK is rectangular in shape with dimensions of 90 cm x 180 cm and a width of 70 cm. Tool testing was carried out at the Electrical Laboratory of Trunojoyo University for 180 minutes. While the process of collecting data from the test results is carried out every 5 minutes, so as to get a total of 36 data. The data that can be taken in testing the tool is working pressure, temperature in the pipe, voltage, and working current. Analysis of the test results in the form of compressor work (Wk), heat released by the condenser (Qout), heat absorbed by the evaporator (Qin), Coefficient of Performance (COP), Power (P), and efficiency. The average values ​​obtained from the results of data calculations include: the value of the compressor work is 17.11 kJ/kg, the heat released by the condenser is 180.71 kJ/kg, the heat absorbed by the evaporator is 163.57 kJ/kg, the value COP of 9.56, apparent power and active power of 430.29 VA and 395.86 Watt, and an efficiency value of 12.26. The results of the analysis obtained from testing the props and the data calculation process can be concluded that the air conditioning machine is able to work optimally and has a good efficiency value in accordance with the unit specifications